Direct imprinting of indium–tin-oxide precursor gel and simultaneous formation of channel and source/drain in thin-film transistor. (17th January 2018) - Haga, Ken-ichi; Kamiya, Yuusuke; Tokumitsu, Eisuke
Abstract: We report on a new fabrication process for thin-film transistors (TFTs) with a new structure and a new operation principle. In this process, both the channel and electrode (source/drain) are formed simultaneously, using the same oxide material, using a single nano-rheology printing (n-RP) process, without any conventional lithography process. N-RP is a direct thermal imprint technique and deforms oxide precursor gel. To reduce the source/drain resistance, the material common to the channel and electrode is conductive indium–tin-oxide (ITO). The gate insulator is made of a ferroelectric material, whose high charge density can deplete the channel of the thin ITO film, which realizes the proposed operation principle. First, we have examined the n-RP conditions required for the channel and source/drain patterning, and found that the patterning properties are strongly affected by the cooling rate before separating the mold. Second, we have fabricated the TFTs as proposed and confirmed their TFT operation.